The Effects of COVID-19 on Labour Market Matching in Austria: A Regional and Sectoral Perspective - Michael Christl; Aron Kiss; Wolfgang Nagl (Global Labor Organization (GLO), 2024)
This paper examines labour market matching in Austria since 2008, with a particular focus on the effects of the COVID-19 pandemic at the regional and sectoral level. We use comprehensive monthly administrative data and apply a standard matching model to estimate Beveridge curves for different labour market segments. Despite the disruptive effects of the COVID-19 pandemic, overall labour market conditions were relatively stable, with mismatched unemployment returning to pre-pandemic levels. This return to prepandemic levels is confirmed at the regional level. However, a sectoral analysis, as well as a sectoral regional analysis, reveals lasting effects in the hospitality and health care sector.
Keywords: J21; J64; 330; Beveridge curve; unemployment; matching efficiency; COVID-19